Motivational processes in physical education and objectively measured physical activity among adolescents - Hanna Kalajas-Tilga; Andre Koka; Vello Hein; Henri Tilga; Lennart Raudsepp (Elsevier, 2020)
Purpose: Grounded in self-determination theory (SDT), the present study tested how students' perceptions of autonomy support from physical education teachers predicts objectively measured moderate-to-vigorous physical activity (MVPA) of adolescents. According to SDT, it was expected that psychological needs and autonomous and controlled forms of motivation would mediate these relationships. Methods: Students (n = 397) aged from 11 to 15 years in 17 different schools filled in questionnaires regarding SDT variables. In addition, objective MVPA was measured using an accelerometer (ActiGraph GT3X; ActiGraph, Pensacola, FL, USA) for 7 days. Structural equation modelling was used to examine the hypothesized relationships among the study variables. Results: The theory-based model showed a good fit with the data: χ2 = 642.464, df = 257; comparative fit index = 0.932; non-normed fit index = 0.921; root mean square error of approximation = 0.062; root mean square error of approximation 90% confidence interval: 0.054-0.067. As hypothesized, there was a significant and positive direct relationship between autonomy support and need satisfaction (β = 0.81, p = 0.001). In turn, need satisfaction positively predicted intrinsic motivation (β = 0.86, p = 0.001). Intrinsic motivation was positively related to MVPA (β = 0.29, p = 0.009). A significant indirect effect (β = 0.20, p = 0.004) supported the mediating role of psychological need satisfaction and intrinsic motivation in the relationship between perceived autonomy support and objectively measured MVPA. Conclusion: The findings of the current study support the applicability of the SDT-based model in explaining the antecedents of objectively measured MVPA of adolescents. To enhance adolescents' daily MVPA, special focus should be put on increasing their intrinsic motivation toward physical education.